Avaliação do crescimento e de mecanismos de tolerância à salinidade em plantas de sorgo forrageiro irrigados com águas salinas - Aquino, Alexandre José Silva de (2005)
This work studied the tolerance of two genotypes of forrage sorghum (Sorghum bicolor (L) Moench), one salt sensitive (CSF 18) and another salt tolerant (CSF 20). Selected seeds were germinated in vases containing 12 Kg of sandy soil under greenhouse conditions. Ten days after seeding, plants were irrigated with different salt concentration water. For prepairing saline solutions, NaCl, CaCl2.2H2O e MgCl2.6H2O salts were used solved in destyled water, on proportion 7:2:1. the randomized completely design was used, and the treatments were outlined according to a 2 x 5 factorial arrangment, composed with two genotypes and five tratments of increasing salinity (0.5, 2.0 , 4.0, 6.0 e 8.0 dS.m-1), with five replicates. During vegetative growth measures of photosyntesis and gas exchanges were made. Fourty four days after germination, plants were harvested. The contents measured were morpholocial characteristics, shoot fresh and dry matter production (leaves, blades and colms) and water potential. Roots were colected with soil samples in three deaphts (10, 20 e 30 cm). Solute contents of shoot and soil samples were determinated. The genotype CSF 20 showed higher values of internode number, plant height and colm diameter. The reductions of growth were higher for CSF 18 genotype, when plants were exposed to the higher salt levels irrigation water. The relation of K+ in colms and leaves were lower in genotype CSF 20, sugesting that this genotype shows a higher capacity of distribution of K+ in leaves. The genotype CSF 20 showed higher accumulation of soluble carbohydrates in leaves. Results showed that CSf 18 genotype was most sensible to water salinity and CSF 20 was most tolerant to water salinity.